PENERAPAN MODEL PEMBALAJARAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN PARAKARYA DAN PRODUK KREATIF - Dina Aulia; Wyanet Putri Alisha; Kafyanti Nurmeli; Armiati Armiati; Dessi Susanti (Universitas Negeri Medan, 2023)
Abstract : Implementation of Problem Based Learning Model in Crafts and Creative Products Subject. The world of education currently requires innovative learning models, one of which is the Problem Based Learning model. This research is action research which aims to: 1) Find out whether the implementation of the Problem Based Learning learning model can improve student learning outcomes. 2) Knowing whether the implementation of the PBL model can increase student learning participation. 3) Knowing of the implementation of the PBL model can improve the ability to convey ideas. The research subjects were XI grade students in the subject of Crafts and Creative Products at SMK 1 Padang Panjang. This research was conducted in two cycles consisting of planning, implementation, observation/ evaluation, and reflection by implementing the Problem Based Learning model. This research resulted in the implementation of Problem Based Learning which has an effect on increasing learning outcomes, student participation, and the ability to giving ideas. The implementation of the PBL model is effectively applied by teachers in learning that aims to improve student learning experiences. Suggestions for the future so that teachers can use a more varied learning model.Keyword : Problem Based Learning, Entrepreneurship, Creativity, Action Research. Abstrak : Penerapan Model Pembalajaran Problem Based Learning dalam Pembelajaran Parakarya dan Produk Kreatif. Dunia pendidikan saat ini memerlukan model pembelajaran yang inovatif salah satunya model pembelajaran Problem Based Learning. Penelitian ini berjenis penelitian tindakan kelas yang bertujuan untuk : 1) Mengidentifikasi implementasi model pembelajaran PBL apakah dapat meningkatkan hasil belajar, partisipasi belajar, dan kemampuan menyampaikan ide/ gagasan siswa, . Subjek penelitian yaitu siswa kelas XI pada mata pelajaran Prakarya dan Produk Kreatif di SMK 1 Padang Panjang. Penerapan PBL ini dilakukan sebanyak dua siklus yang terdiri dari perencanaan, pelaksanaan, observasi/ evaluasi, dan refleksi dengan mengimplementasikan model pembelajaran PBL. Penelitian ini menghasilkan penerapan pembelajaran PBL berpengaruh terhadap peningkatan hasil belajar, partisipasi siswa, dan kemampuan menyampaikan ide/ gagasan. Sehingga penerapan model pembelajaran PBL efektif diterapkan guru dalam pembelajaran yang betujuan untuk meningkatkan pengalaman belajar siswa. Saran untuk kedepannya agar guru dapat menemukan, mengembangkan dan menerapkan model pembelajaran yang lebih variatif.Kata Kunci : Problem Based Learning, Kewirausahaan, Kreatifitas, Penelitian Tindakan Kelas